An improved time reversal mirror based on standard linear frequency modulation waveform - Yongkang Wang (Nature Portfolio, 2021)
Abstract Time reversal mirror (TRM) technology is the adaptive focusing method evolved from the phase conjugate method in optics. Conventional incentive method in TRM technology is a narrow pulse signal with a high bandwidth. In this paper, the autocorrelation property of the TRM was proved from the time-reversal symmetry of the wave equation. The linear frequency modulation (LFM) signal is adopted as the exciting signal in the TRM, which gives the dual autocorrelation function waveform, including the exciting signal and transport channel response. Theoretical results show that the peak value of the transducer array’s focusing signal is determined by the pulse width of the LFM signal and the number of array elements. In addition, the adaptive filtering deconvolution method is used to precisely regulate the input signal to ensure that the final detecting signal is the expected LFM waveform, which eliminates the effect of the transport channel and enhances matched filtering effects. The results hold great theoretical significances for the development of TRM technology in ultrasonic detection.